Pengaruh Motivasi Kerja, Budaya Kerja dan Kepemimpinan terhadap Kinerja Pegawai Departemen Perindustrian dan Perdagangan Provinsi Maluku Ambon - Laurens, Samson (Patria Artha Management Journal, 2017)
This study aims to determine the effect of partial and simultaneous, work motivation factors, work culture, and leadership on the performance of civil servants in the Ministry of Industry and Trade of Maluku Province Ambon. The population that became the unit of analysis in this study, is the civil servants in the Ministry of Industry and Trade of Maluku Ambon as many as 86 people. For this research, the sampling technique used is by proportional stratified random sampling. The data that has been collected is processed by descriptive analysis and inferential analysis. Descriptive statistical analysis is used to describe the data characteristics obtained for each variable. Inferential analysis is used to test the hypotheses that have been formulated. The analysis technique used is multiple linear regression analysis. Based on the results of the analysis known that work motivation, work culture, and leadership simultaneously can give a positive and significant influence to the performance of civil servants at the Ministry of Industry and Trade Maluku Province Ambon. Partially only variable of work motivation which have significant effect. Therefore, the management of human resources development in decision making related to the improvement of the performance of employees at the Ministry of Industry and Trade of Maluku Province Ambon can maintain and encourage employee work motivation, work culture and leadership so that in turn will further encourage the performance improvement of employees of the Ministry of Industry and Trade Maluku Province Ambon